The causal effect of two occupational factors on osteoarthritis and rheumatoid arthritis: a Mendelian randomization study - Huang, Jian (Frontiers in Public Health, 2024)
Background: Osteoarthritis (OA) and rheumatoid arthritis (RA) are two common types of arthritis. We conducted a two-sample Mendelian randomization (MR) study to estimate the causal effects of two common occupational factors including job involves heavy manual or physical work and job involves mainly walking or standing on OA and RA in individuals of European ancestry. Methods: Instruments were chosen from genome-wide association studies (GWAS) that identified independent single nucleotide polymorphisms (SNPs) robustly linked to job involves heavy manual or physical work (N=263,615), as well as job involves mainly walking or standing (N=263,556). Summary statistics for OA and RA were taken from the IEU GWAS database; both discovery and replication GWAS datasets were considered. The primary analysis utilized the inverse variance weighted (IVW) MR method, supplemented by various sensitivity MR analyses. Results: In the IVW model, we found that genetically predicted job involves heavy manual or physical work was significantly associated with OA in both the discovery (odds ratio [OR]=1.034, 95% confidence interval [CI]: 1.016-1.053, P=2.257×10-4) and the replication (OR=1.857, 95% CI: 1.223-2.822, P=0.004) analyses. The causal associations were supported in diverse sensitivity analyses. MR analyses suggested no causal effect of genetically predicted job involves heavy manual or physical work on RA. Similarly, our data provided no evidence that genetically predicted job involves mainly walking or standing was related to OA and RA. Conclusions: Our MR study suggests that job involves heavy manual or physical work is a risk factor for OA. It is of utmost importance to create preventive strategies aimed at reducing its impact on OA at work sites.